Higher plasma viremia in the febrile phase is associated with adverse dengue outcomes irrespective of infecting serotype or host immune status: an analysis of 5642 Vietnamese cases - Vuong, NL; Quyen, NTH; Tien, NTH; Tuan, NM; Kien, DTH; Lam, PK; Tam, DTH; Van Ngoc, T; Yacoub, S; Jaenisch, T; Geskus, RB; Simmons, CP; et al. (Oxford University Press, 2020)
Background: One of the generally accepted constructs of dengue pathogenesis is that clinical disease severity is at least partially dependent upon plasma viremia, yet data on plasma viremia in primary versus secondary infections and in relation to clinically relevant endpoints remain limited and contradictory.